PRELIMINARY ASSESSMENT OF PARTICULATE CONCENTRATION NEAR COAL FIRED POWER PLANT - VUJIĆ, Bogdana; PODE, Vasile; MIĆIĆ, Jelena; POPESCU, Francisc; MARČETA, Una; CIOABLA, Adrian Eugen (Studia Universitatis Babeș-Bolyai Chemia, 2020)
This study shows the results of preliminary monitoring of particulate matter (PM10 and PM2.5) at four measurement points, during the three campaigns (spring, autumn, winter) The study was conducted for the first time in residential area near coal-fired power plant, Ugljevik, Bosnia and Herzegovina. The power plant flue gas cleaning equipment in the time of this research was out of the function. Authors investigated seasonal variations of PMs concentration levels, influence of terrain structure and meteorological condition on PMs distribution and identification of PMs origin sources. The results revealed that seasonal variation was more expressed in the case of PM2.5 concentration, while for PM10, occasionally episodic pollution (399µg/m³) was recorded. Also, it was noted that prevailing meteorological conditions and surrounding terrain structure could have limiting effect on PMs dispersion. In order to detect PMs origin, linear regression analysis was applied. Authors revealed that PM2.5 originating from power plant could be prescribed partly for M1 where the greatest correlation was calculated (R2=0,45). Although the measuring sites were set in proper position regarding dominant winds and terrain structure, it was identified that certain measurement sites were affected by the other local particulate matter sources, especially in case of PM10.